Effect of inositol "analogues" on the production of myo-inositol-1-phosphate synthase in Neurospora crassa slime strain. - A. Kiss; M. Schablik; A. Zsindely; G. Szabo (Fungal Genetics Reports, 1988)
Effect of inositol "analogues" on the production of myo-inositol-1-phosphate synthase in Neurospora crassa slime strain.